DIFFERENCES IN DMF-T INDEX OF PDAM WATER AND RIVER WATER USERS IN THE BLACKSMITH INDUSTRY AREA - Raihatun Nida; Ika Kusuma Wardani; Sherli Diana; Juliyatin Putri Utami; Norlaila Sarifah (FKG ULM, 2025)
Background: Caries is a disease of the oral cavity that affects the hard tissues of the teeth, enamel, dentin, and cementum. Caries is a multifactorial disease or is caused by many factors. One factor that influences the incidence of caries is the water used for daily purposes. Water containing high concentrations of metals can affect the incidence of caries, one of which is iron. Ferrum or iron contained in water can cause caries by increasing H + ions and then continuing to decrease pH, resulting in a demineralization or dissolution process of hydroxyapatite. Caries occurrence can be measured using the DMF-T index. Purpose: This study aims to determine the difference in the DMF-T index of students using PDAM water and river water in the iron industry area of Sungai Pinang Village. Methods: The method used was analytic observational with a cross-sectional design. Respondents in this study were 36 for each group, with a total of 72 respondents. Results: The results of the unpaired T-Test test showed a significance value of 0.00 <0.05, so HO was rejected. Conclusion: There is a significant difference in the DMF-T index of river water PDAM water users in the blacksmith industrial area of Sungai Pinang Village.